PERSEPSI PENGUSAHA USAHA MIKRO KECIL DAN MENENGAH (UMKM) TERHADAP PENERAPAN AKUNTANSI DI KOTA LUBUKLINGGAU - Aning Kusuma Putri; Dewi Anggraini (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2016)
This study aims to determine the perception of entrepreneurs of small and medium micro enterprises on the application of accounting in Lubuklinggau 2013. The object of this study was taken from UMKM in Lubuklinggau, totaling 66 UMKM. The type of data used was primary data obtained by distributing questionnaires. This study uses data processing with multiple regression with SPSS16.0 (statistical computer program). From the tests we can conclude the results of multiple linear regression quation to obtain Y= 0,412 + 0,206x1 + 0,156x2 + 0,199x3 + 0,161x4 which means psychological, family, internal factors and external factors can give effect to the application of accounting. The value of the correlation coefficient is R2=0.641means that 64.1% variation changes the dependent variable can be explained by the independent variable, while the remaining 35.9% is explained by other variables not included in this study. Partially (t test), all independent variables have an influence on the dependent variable, it is intended by tvalue>ttable. Concurrently (simultaneously) psychological, family,internal factors and external factors have a significant impact on the application of accounting. Results of analysis showed that the calculated Fvalue of 21.428 and Ftable at 2.37. This shows that Fvalue>Ftable and also sig0.000<0.05.